Perceived employee-organization congruence and job performance: A study of machine operators in Sri Lankan apparel sector - Perera, G. D. N.; Khatibi, Ali; Nawaratne, N.N.J. (My University, 2013)
This study was conducted to measure the impact of perceived employeeâ organization congruence (PEOC) on job performance of machine operators in Sri Lankan apparel sector. It was previously reported that PEOC to have a significant impact on job performance of employees in various business sector. In view of the importance of the apparel sector in the economic development of Sri Lanka, hence the focus of this study is to discover whether similar impact exist among the machine operators of the Sri Lankan apparel sector. A quantitative method was employed and data were collected using structured questionnaire in the five garment factories. Simple random sampling was applied to select a representative sample. There were 175 questionnaires distributed and 160 returned questionnaires were deemed usable for further analysis resulted in 91% response rate. It was found that the measurement scales met the acceptable standards of validity and reliability analyses. Correlation analysis and regression analysis were used to test the research hypothesis. Study confirmed that PEOC is significantly correlated with job performance. Though PEOC is a significant predictor of job performance, it can be concluded that too little or too much of PEOC leads to have low level of job performance and moderate level of PEOC leads to have high level of job performance, in the tested domain.